2019
DOI: 10.32725/jab.2019.001
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy as major risk factor of falls - analysis of 12 months experience in hospitals in South Bohemia

Abstract: This study aimed to analyze the effect of fall risk-increasing drugs (FRIDs) and drug-related factors relative to falls through clinical pharmacy service in hospitalized patients, focusing on the relevance of clinical pharmacist evaluation in the context of physician assessment. A prospective study of inpatient falls was conducted in 2017 retrieving data from 4 hospitals in South Bohemia, Czech Republic. An online database was developed to collect patient and fall-related data, and fall evaluation records. Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…According to our findings, the fall risk assessment tool presented in this study could be helpful to prevent medication-related falls and increase quality of geriatric care in health care institutions. This is supported by the findings of previous studies that have reported the medication use as a remarkable but modifiable fall risk factor [ 48 , 50 ]. Therefore, it is reasonable to implement a strategy to avoid use of fall risk-increasing drugs in the routine practice in geriatric care units.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…According to our findings, the fall risk assessment tool presented in this study could be helpful to prevent medication-related falls and increase quality of geriatric care in health care institutions. This is supported by the findings of previous studies that have reported the medication use as a remarkable but modifiable fall risk factor [ 48 , 50 ]. Therefore, it is reasonable to implement a strategy to avoid use of fall risk-increasing drugs in the routine practice in geriatric care units.…”
Section: Discussionsupporting
confidence: 88%
“…The increased fall risk is also evidenced in patients using opioids (OR = 1.61), antiepileptics (OR = 1.55), anti-Parkinson drugs (OR = 1.54), and NSAIDs (OR = 1.09) [ 46 , 47 ]. Furthermore, the previous study from Czech Republic (Maly et al [ 48 ]) classified drugs that affected to the nervous system (antipsychotics, antidepressants, analgesics) and to the cardiovascular system (diuretics, beta blocking agents, agents acting on the renin-angiotensin system) as the most frequently used fall risk-increasing drugs in hospitals. Thus, many studies have reached similar conclusions, although the fall-increasing medicines have been presented slightly in different order.…”
Section: Discussionmentioning
confidence: 99%
“…This association between the use of potentially inappropriate medications and falls in older adults is stronger in the presence of more comorbidities, which results in the prescription of more medications ( Johnell and Fastbom, 2008 ) and increases the probability of pharmacologic interactions and other problems related to medications. A correct pharmacotherapeutic evaluation of a hospitalized patient, especially a patient aged ≥65 years and with polypharmacy, can identify inappropriate or risky prescriptions and can reveal the probability of suffering a fall and the potential need to avoid particular higher-risk medications ( Maly et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%